2023
DOI: 10.3390/ijerph20032077
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Effects of Perceived Damage Caused by Harmful Rumors about Fukushima after the Nuclear Accident and Information Sources and Media

Abstract: The nuclear accident that accompanied the Great East Japan Earthquake of 11 March, 2011, was also an information disaster. A serious problem that arose after the accident and persisted for a long time was the damage caused by harmful rumors (DCBHR). In 2016, a cross-sectional questionnaire survey on health and information was conducted in Fukushima. The eligible population of this survey was 2000 Fukushima residents, which included those in the evacuated areas. We received 861 responses. Data were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A previous study clearly showed that people whose opinions opposed those officially recognized by international organizations had often gathered information from social media and other internet sources. These sources claimed that radioactivity would cause serious and various health problems for children [22,23]. Additionally, some individuals believe that the nosebleeds, coughs, and skin symptoms that appeared after the FDNPP accident were caused by radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study clearly showed that people whose opinions opposed those officially recognized by international organizations had often gathered information from social media and other internet sources. These sources claimed that radioactivity would cause serious and various health problems for children [22,23]. Additionally, some individuals believe that the nosebleeds, coughs, and skin symptoms that appeared after the FDNPP accident were caused by radiation exposure.…”
Section: Discussionmentioning
confidence: 99%